Study of Investment Knowledge in Rural Setting: The Effect Financial Literacy and Minimum Capital on Investment Interest - khanifah, khanifah; Aprilia, Ivana; Triyani, Agus; Melo, Tania Marie P (Universitas Muhammadiyah Semarang, 2026)
This study examined the influence of investment knowledge, financial literacy, and minimum capital requirement on investment intention among communities in Bawang Regency, Indonesia. Although retail investor participation was increasing nationally, investment engagement at the local level remains limited, particularly in semi-urban areas with limited access to financial information and investment services. Using a quantitative approach, data were collected from 115 purposively selected respondents through a structured questionnaire measured on a five-point Likert scale. A multiple linear regression analysis in SPSS version 26 was conducted to investigate the predictive effects of these three factors on investment intentions. The results indicated that investment knowledge and minimum capital requirements significantly increase investment intentions, whereas financial literacy did not have a statistically significant effect. These findings suggest that domain-specific investment competencies and affordability, rather than general financial skills, were the primary drivers of investment intentions in rural-semi-urban communities. This study extended the Theory of Planned Behavior by highlighting the roles of cognitive ability and perceived feasibility in shaping investment decisions, and it provided practical insights for policymakers and financial institutions to design targeted investment education and accessibility initiatives. Urban or rural demographics were proposed as factors that strengthen or weaken the relationship between investment knowledge and investment intentions. Local government support for local investors was needed to balance the growth of foreign investment in the Batang District, Indonesia.